PENINGKATAN KOMPETENSI PROFESIONAL DOSEN MELALUI PENDIDIKAN DAN PELATIHAN PADA AKADEMIK KEPERAWATAN (AKPER) YAPENAS 21 DI KABUPATEN MAROS - muh. ichlasul amal.s; Syahrir; Ibrahim Syah (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2025)
This study was intended to determine the increasing the professional competence of lecturers through education and training at the Yapenas 21 Nursing Academy (AKPER) in Maros Regency. The research method used was qualitative descriptive with a case study approach. Data was obtained through distributing questionnaires to a number of student respondents, interviews with lecturers, staff and students at the Nursing Academy (AKPER) Yapenas 21 Maros, by looking at 5 (five) lecturer competencies, namely specialist competency, social competency, individual competency, methodical competency, Spiritual Competency, Specialist Competency, Social Competency. The results of the study showed that overall Specialist Competence reached 57.0%, and was categorized as moderate. Social Competency reached 51.0%, and was categorized as medium, Individual Competency 59.0%, categorized as medium, Methodical Competency 33.0%, categorized as low. Spiritual Competence 65.0%, categorized as moderate. Then an analysis of the increase in professional competency of AKPER YAPENAS 21 Maros lecturers through education and training (Diklat) was carried out. It was found that the increase in specialist competency through training was 72.0%, and was categorized as less improved. Increasing Social Competence through Training is 57.0%, and was categorized as moderate. Increasing Individual Competence through Training 60.0%, categorized as medium. Increasing Methodical Competency through Training 71.0%, categorized as moderate. Increasing Spiritual Competence through Training 45.0%, categorized as low. Then it was concluded that the analysis of the five variables supporting Professional Competency, the achievement of Professional Competency for Lecturers at AKPER YAPENAS 21 Maros after attending Education and Training was 61.0%, and was categorized as moderate.